Non-Bacterial Chronic Recurrent Osteomyelitis of the Clavicle - Pan, K.L.; Chan, W.H; Ong, G.B.; Zulqarnaen, M.; Norlida, D.K (Malaysian Orthopaedic Journal, 2012)
This report details the case of a 12-year-old girl with a painful, progressive swelling of the medial portion of the clavicle with no history of trauma or other constitutional symptoms. All laboratory investigations were normal except for an elevated erythrocyte sedimentation rate (ESR). Initial plain radiographs showed a destructive lesion with magnetic resonance imaging showing features of malignancy. Biopsies revealed osteomyelitis, but with negative bacterial cultures and no evidence of malignancy. Treatment with antibiotics did not result in a favourable response. Over time, the swelling increased in size with episodic exacerbations of pain. Follow-up radiographs showed sclerosis and hyperostosis. After five years, this was recognized as non-bacterial chronic recurrent osteomyelitis of the clavicle.